Pengaruh Sinetron terhadap Sikap Ibu-Ibu Mengenai Peran Ganda Wanita - Rinawati, Rini (Mediator, 2002)
This research was intended to describe the effect ofsinetron "Karmila" exposure on the viewer sabout woman double role. The research was conducted in Bandung, used survey method. and the sample was J20 housewives in Bandung. The result showed that: (1) the content ofmesesage in "Karmila" influenced directly on the viewer attitude about woman doubel role; (2) the presentation ofmesesage in "Karmila" influenced directly on the viewer s attitude about woman doubel role; (3) the content ofmesesage and the presentation of mesesage in "Karmila" influenced directly on the viewer sattitude about woman doubel role.